A preliminary study on the uptake capacity of acid, base and none pretreated for the removal of heavy metals (copper, Cadmium, and lead) from aqueous solution in four test conditions. - Ciudad, Bernadette Rhodes Siason
Gracilariopsis bailinae is abundant in Panay and is used as a primary source of agar. Its abundance and capacity to adsorb heavy metals make it a potential alternative for heavy metal removal in wastewaters., A preliminary study was conducted on the heavy metal uptake capacity of pretreated seaweeds to determine if there is a significant effect in the amount of Cu2+ removed and to find out which among the treatments could give the highest yield. The optimum pH and contact time needed for the highest yield was determined by designing a matrix using the 2raise to the 2nd power factorial design. This yielded four runs equivalent to four test conditions. Based on the optimization data, no significant difference was found between the yields of seaweeds from different pretreatments. The optimum of pH value for CU 2+ removal in aqueous solution was 11.5 while the optimum contact time was at thirty minutes. The Freundlich and Langmuir isotherm were not applicable for the metals and adsorbent used. However, results of teh adsorption analysis showed a relatively high average amount of metal removed from solution with 50-90 percent cadmium, 70-100 percent copper and 20-87 percent lead removed.